MISI GEREJA DI ERA DIGITAL: PEMANFAATAN TEKNOLOGI UNTUK MENJANGKAU GENERASI BARU - Verlis Bintang; Yanti Taruk Tangko, Devi Yanti, Jessica Gloria Padatu, Monicha Datu Palinggi (ADISAM PUBLISHER, 2023)
This research is a literature review that delves into the role of technology in the context of church mission, especially in eflorts to reach and influence the new generation in the digital era. The digital era has transformed how humans interact, learn, and seek information, and churches must also adapt to remain relevant in fulfilling their mission. This study investigates technological developments such as social media, church websites, mobile applications, and streaming platforms, which have become crucial tools in delivering religious messages, teaching, and providing access to church worship. By analyzing existing literature, this research attempts to answer several key questions, such as the extent to which technology has influenced the perception, participation, and acceptance of the new generation towards religious messages. Additionally, this study also explores challenges and opportunities that arise with the use of technology in the church context. The results of this research will provide insights for churches seeking to maximize the use of technology in their mission eflorts and assist in designing eflective strategies to reach the new generation living in the digital world. Furthermore, this research provides a foundation for further studies and practical applications for churches in various contexts